Phosphor powder, composite, and light-emitting device

By using phosphor powder containing CASN and SCASN phosphor particles and optimizing its performance through pressure cooker tests, the problem of insufficient luminescence characteristics and quantum efficiency of existing phosphor powders under high-density light excitation is solved, and higher reliability is achieved. sex and stability.

CN119331606APending Publication Date: 2025-01-21DENKA CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410964322.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-20
Filing Date
2024-07-18
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing phosphor powder has insufficient luminescence characteristics and quantum efficiency maintenance rate under high-density light excitation, which affects reliability.

Method used

Phosphor powder containing CASN phosphor particles and SCASN phosphor particles is used, and the color difference ΔE* is ensured to be below 25.0 through a pressure cooker test to improve the reliability of the phosphor powder.

Benefits of technology

By improving the reliability of phosphor powder, it ensures stability and luminescence performance under high temperature and high humidity conditions, and extends its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331606A_ABST
    Figure CN119331606A_ABST
Patent Text Reader

Abstract

A phosphor powder containing one or more phosphor particles selected from CASN phosphor particles and SCASN phosphor particles, the phosphor powder being characterized in that when a pressure cooker test in which 5 g of the phosphor powder is exposed for 53 hours in an atmosphere at 130 DEG C, a relative humidity of 98%, and 0.16 MPa using a pressure cooker tester, the amount of the phosphor particles in the pressure cooker test is less than the amount of the phosphor particles in the pressure cooker test, and the amount of the phosphor particles in the pressure cooker test being less than the amount of the phosphor particles in the pressure cooker test being less than the amount of the phosphor particles in the pressure cooker test. The color difference [Delta] E * = {(L1 *-L2 *) 2 + (a1 *-a2 *) 2 + (b1 *-b2 *) 2} 1 / 2 between the chromaticity coordinates (L1 *, a1 *, b1 *) of the phosphor powder before the pressure cooker test specified in the CIE 1976L * a * b * color system and the chromaticity coordinates (L2 *, a2 *, b2 *) of the phosphor powder after the pressure cooker test is 25.0 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field The present invention relates to phosphor powder, composite and light-emitting device. Background Art In order to manufacture white LEDs, red phosphors that convert blue light from a blue LED chip into red light have been studied. As red phosphors, so-called CASN phosphors, SCASN phosphors, and the like are known. Patent Document 1 discloses a phosphor having excellent luminescent properties even when excited by high-intensity light, wherein the half-peak width of the luminescent spectrum is narrow and the quantum efficiency maintenance rate of luminescence is high, and the phosphor is characterized by comprising a general formula M a Sr b Ca c Al d Si e N f Represents the crystal phase, 4000mW / mm 2 The quantum efficiency maintenance rate under light excitation is 85% or more. In the general formula, M represents an activating element, 0<a<0.05, 0.95≤b≤1, 0≤c<0.1, a+b+c=1, 0.7≤d≤1.3, 0.7≤e≤1.3, 2.5≤f≤3.5. Prior art literature Patent Literature Patent Document 1: Japanese Patent Application Publication No. 2019-077800 Summary of the invention The present invention provides phosphor powder with improved reliability, and a composite and a light-emitting device using the phosphor powder with improved reliability. The present inventors have conducted intensive research to solve the above problems. As a result, they found that the color difference ΔE before and after the pressure cooker test is * The present invention was completed by finding that the reliability can be improved by phosphor powder within a specific range. According to the present invention, there are provided the phosphor powder, composite, and light-emitting device shown below.

[0001] A phosphor powder comprising one or more phosphor particles selected from CASN phosphor particles and SCASN phosphor particles, When a pressure cooker test was conducted by exposing 5 g of the phosphor powder to an atmosphere of 130° C., 98% relative humidity, and 0.16 MPa for 53 hours using a pressure cooker tester, CIE1976L * a * b *The chromaticity coordinates (L1 * 、a1 * 、b1 * ) and the chromaticity coordinates (L2 * 、a2 * 、b2 * ) color difference ΔE * ={(L1 * -L2 * ) 2 +(a1 * -a2 * ) 2 +(b1 * -b2 * ) 2} 1 / 2 Below 25.0.

[0002] The phosphor powder according to [1], wherein the above (L1 * -L2 * ) 2 Below 65.0.

[0003] The phosphor powder according to [1] or [2], wherein the above (a1 * -a2 * ) 2 Below 260.0.

[0004] The phosphor powder according to any one of [1] to [3], wherein the above (b1 * -b2 * ) 2 Below 300.0.

[0005] The phosphor powder according to any one of [1] to [4], comprising a phosphor of the general formula Eu a Sr b Ca c Al d Si e N f O g It represents phosphor particles with 0<a<1.00, 0<b<1.00, 0<c<1.00, 0.70<a+b+c<1.30, 0.70<d<1.30, 0.70<e<1.30, 0<f<3.00, 0<g<3.00, and 2.50<f+g<3.50.

[0006] The phosphor powder according to [5], wherein a<0.30.

[0007] The phosphor powder according to [5] or [6], wherein b>0.50.

[0008] The phosphor powder according to any one of [5] to [7], wherein the molar ratio of b / (b+c) of the phosphor powder is 0.96 to 0.99.

[0009] The phosphor powder according to any one of [1] to [8], wherein the volume-based median diameter D of the phosphor powder based on a laser diffraction scattering method is 50 1μm~40μm.

[0010] The phosphor powder according to any one of [1] to [9], wherein a relative fluorescence intensity reduction rate of the phosphor powder according to the following method 2 is 10.0% or less. (Method 2) Let the relative fluorescence intensity of the phosphor powder measured by a spectrophotometer be Y1(%), and let the relative fluorescence intensity of the phosphor powder after 5 g of the phosphor powder is kept at 130°C, 98% relative humidity, and 0.16 MPaG for 53 hours using a pressure cooker testing machine be Y2(%), then 100×(Y1-Y2) / Y1 be the relative fluorescence intensity reduction rate (%).

[0011] The phosphor powder according to

[10] , wherein the Y1 is 150% or more.

[0012] The phosphor powder according to any one of [1] to

[11] , wherein the phosphor powder has an absorptivity reduction rate of 5.0% or less for light of a wavelength of 455 nm according to the following method 3. (Method 3) Let the absorptivity of the phosphor powder to light of wavelength 455 nm measured by a spectrophotometer be Z1(%), let the absorptivity of the phosphor powder to light of wavelength 455 nm after keeping 5 g of the phosphor powder at 130°C, 98% relative humidity and 0.16 MPaG for 53 hours using a pressure cooker testing machine be Z2(%), then let 100×(Z1-Z2) / Z1 be the absorptivity reduction rate (%).

[0013] The phosphor powder according to

[12] , wherein the Z1 is 90.0% or more.

[0014] A composite body comprising: the phosphor powder according to any one of [1] to

[13] , and a sealing material sealing the phosphor powder.

[0015] The composite according to

[14] , wherein the sealing material comprises one or more selected from silicone resin, epoxy resin, polyurethane resin, glass and ceramic.

[0016] A light-emitting device comprising: a light-emitting element that emits excitation light, and the complex described in

[14] or

[15] that converts the wavelength of the excitation light. According to the present invention, it is possible to provide phosphor powder having improved reliability, and a composite and a light-emitting device using the phosphor powder having improved reliability. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 This is a schematic cross-sectional view schematically showing an example of the structure of a light emitting device. Explanation of symbols 1Phosphor powder 30 Sealing material 40 complex 100 Lighting Devices 120 light emitting elements 130 heat sink 140 Shell 150 1st lead frame 160 2nd lead frame 170 bonding wire 172 bonding wire DETAILED DESCRIPTION Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings. In the drawings, the same components are denoted by the same reference numerals, and the description thereof will be appropriately omitted. In order to avoid redundancy, when there are a plurality of identical components in the same drawing, only one of them may be denoted by a reference numeral instead of all of them. The drawings are for illustration purposes only. The shapes, dimensional ratios, etc. of the components in the drawings do not necessarily correspond to actual products. In the present embodiment, "A to B" indicating a numerical range means A or more and B or less unless otherwise specified. <Phosphor powder> The phosphor powder of this embodiment includes one or more phosphor particles selected from CASN phosphor particles and SCASN phosphor particles. In addition, from the viewpoint of further improving the fluorescence characteristics of the phosphor powder, the phosphor powder of this embodiment preferably includes SCASN phosphor particles. The CASN phosphor particles of this embodiment are composed of (Si, Al)-N4 regular tetrahedral bonds, with Ca atoms located in the gaps of the skeleton. 2+ Part of Eu is used as a luminescent center 2+Phosphor particles obtained by replacing activation elements. The SCASN phosphor particles of this embodiment are composed of (Si, Al)-N4 regular tetrahedral bonds, and some of the Ca atoms in the gaps of the skeleton are replaced by Sr atoms and solid-dissolved, thereby Ca 2+ Part of Eu is used as a luminescent center 2+ Phosphor particles obtained by replacing activation elements. Color difference ΔE of the phosphor powder of this embodiment before and after the pressure cooker test * Below 25.0. Here, the color difference ΔE * The pressure cooker test was conducted by exposing 5 g of phosphor powder to an atmosphere of 130°C, 98% relative humidity, and 0.16 MPa for 53 hours using a pressure cooker tester. * a * b * The chromaticity coordinates of the phosphor powder before the pressure cooker test specified in the colorimetric system (L1 * 、a1 * 、b1 * ) and the chromaticity coordinates of the phosphor powder after the pressure cooker test (L2 * 、a2 * 、b2 * ) is calculated by the following formula. E * ={(L1 * -L2 * ) 2 +(a1 * -a2 * ) 2 +(b1 * -b2 * ) 2} 1 / 2 According to the research conducted by the present inventors, it was found that the color difference ΔE of the phosphor powder before and after the pressure cooker test was * There is a correlation with the reliability of phosphor powder. The inventors of the present invention have conducted further studies based on the above findings and found that when a pressure cooker test is performed using a pressure cooker tester in which 5 g of phosphor powder is exposed to an atmosphere of 130°C, 98% relative humidity, and 0.16 MPa for 53 hours, the CIE 1976L * a * b * The color value of the phosphor powder before the pressure cooker test specified in the color system (L1 * 、a1 * 、b1 *) and the color value of the phosphor powder after the pressure cooker test (L2 * 、a2 * 、b2 * ) color difference ΔE * The present invention was completed by making the range of 25.0 or less to improve the reliability of the phosphor powder. From the viewpoint of further improving the reliability of the phosphor powder, the color difference ΔE of the phosphor powder of this embodiment is * It is preferably above 0.0, more preferably above 0.5, further preferably above 1.5, further preferably above 2.0, further preferably above 2.5, and is below 25.0, preferably below 23.0, more preferably below 21.0, further preferably below 20.0, further preferably below 19.0, further preferably below 17.0, further preferably below 15.0, further preferably below 12.0, further preferably below 10.0, further preferably below 8.0, further preferably below 7.0. From the viewpoint of further improving the reliability of the phosphor powder, the phosphor powder of this embodiment (L1 * -L2 * ) 2 It is preferably greater than 0.0, more preferably greater than 0.1, and is preferably less than 65.0, more preferably less than 50.0, further preferably less than 40.0, further preferably less than 30.0, further preferably less than 25.0, further preferably less than 20.0, further preferably less than 15.0, further preferably less than 10.0, further preferably less than 5.0, further preferably less than 2.0, further preferably less than 1.0. From the viewpoint of further improving the reliability of the phosphor powder, the phosphor powder of this embodiment (a1 * -a2 * ) 2 It is preferably greater than 0.0, more preferably greater than 0.1, further preferably greater than 0.3, and is preferably less than 260.0, more preferably less than 220.0, further preferably less than 150.0, further preferably less than 100.0, further preferably less than 50.0, further preferably less than 10.0, further preferably less than 5.0, further preferably less than 4.0. From the viewpoint of further improving the reliability of the phosphor powder, the phosphor powder of this embodiment (b1 * -b2 * ) 2It is preferably greater than 0.0, more preferably greater than 0.5, further preferably greater than 1.0, and is preferably less than 300.0, more preferably less than 250.0, further preferably less than 200.0, further preferably less than 150.0, further preferably less than 120.0, further preferably less than 100.0, further preferably less than 90.0, further preferably less than 70.0, further preferably less than 50.0, further preferably less than 40.0, further preferably less than 30.0. In this embodiment, the color difference ΔE before and after the pressure cooker test of the phosphor powder is measured. * The following method can be mentioned, for example. First, use a colorimeter to measure the CIE1976L color of the phosphor powder under the conditions of C light source and 2° viewing field. * a * b * The chromaticity coordinates specified in the color system (L1 * 、a1 * 、b1 * ). Then, the CIE1976L of the phosphor powder was measured in the same manner after a pressure cooker test was performed using a pressure cooker tester to expose 5 g of the phosphor powder to an atmosphere of 130°C, 98% relative humidity, and 0.16 MPa for 53 hours. * a * b * The chromaticity coordinates specified in the color system (L2 * 、a2 * 、b2 * ). Then, (L1 * -L2 * ) 2 、(a1 * -a2 * ) 2 and (b1 * -b2 * ) 2 Then, ΔE is calculated by the following formula: * . E * ={(L1 * -L2 * ) 2 +(a1 * -a2 * ) 2 +(b1 * -b2 * ) 2} 1 / 2 The phosphor powder of this embodiment can be obtained by appropriately selecting the selection of raw materials, the ratio of each raw material, the manufacturing steps and manufacturing conditions. For the selection of raw materials and the ratio of the raw materials, preferably, a large amount of raw materials containing Sr, the addition of the "core" described later, etc. can be used. For the manufacturing steps and manufacturing conditions, preferably, atmospheric heating treatment under appropriate conditions, calcination and annealing using a sealed container, etc. can be used. The details of these will be described later. (Crystal structure, elemental composition, etc.) The phosphor particles of this embodiment are composed of a general formula Eu having the same crystal phase as CaAlSiN3. a Sr b Ca c Al d Si e N f O g In the general formula, 0<a<1.00, 0<b<1.00, 0<c<1.00, 0.70<a+b+c<1.30, 0.70<d<1.30, 0.70<e<1.30, 0<f<3.00, 0<g<3.00, 2.50<f+g<3.50. The crystalline phase can be confirmed by powder X-ray diffraction. The crystalline phase is preferably a single phase of the crystal, but may also include a heterogeneous phase as long as it does not have a significant effect on the phosphor properties. The presence or absence of a heterogeneous phase can be distinguished, for example, by using powder X-ray diffraction based on the presence or absence of peaks other than the peak based on the target crystalline phase. From the viewpoint of improving the fluorescence characteristics of the phosphor powder, a is preferably 0.01<a, more preferably 0.03<a, further preferably 0.05<a, further preferably 0.06<a, further preferably 0.07<a, and preferably a<0.30, more preferably a<0.25, further preferably a<0.20, further preferably a<0.15, further preferably a<0.10. From the viewpoint of improving the fluorescence characteristics of the phosphor powder, b is preferably 0.50<b, more preferably 0.60<b, further preferably 0.70<b, further preferably 0.80<b, further preferably 0.83<b, and preferably b<0.99, more preferably b<0.95, further preferably b<0.90. As another index of the “large amount of Sr”, from the viewpoint of improving the fluorescence characteristics of the phosphor powder, the molar ratio of b / (b+c) is preferably 0.96 or more, more preferably 0.97 or more, further preferably 0.98 or more, and preferably 0.99 or less. Regarding c, from the viewpoint of improving the fluorescence characteristics of the phosphor powder, 0<c, preferably c<0.20, more preferably c<0.15, further preferably c<0.10, further preferably c<0.05, further preferably c<0.03. From the viewpoint of improving the fluorescence characteristics of the phosphor powder, d is preferably 0.80<d, more preferably 0.85<d, further preferably 0.90<d, further preferably 0.95<d, and preferably d<1.20, more preferably d<1.15, further preferably d<1.10, further preferably d<1.05. From the viewpoint of improving the fluorescence characteristics of the phosphor powder, e is preferably 0.75<e, more preferably 0.80<e, further preferably 0.85<e, further preferably 0.90<e, and preferably e<1.20, more preferably e<1.10, further preferably e<1.05, further preferably e<1.00, further preferably e<0.97. For f, from the viewpoint of improving the fluorescence characteristics of the phosphor powder, it is preferably 2.55<f, more preferably 2.60<f, further preferably 2.65<f, further preferably 2.70<f, further preferably 2.75<f, and preferably f<3.40, more preferably f<3.20, further preferably f<3.10, further preferably f<3.00, further preferably f<2.90, further preferably f<2.85, further preferably f<2.82. From the viewpoint of improving the fluorescence characteristics of the phosphor powder, g is preferably 0.01<g, more preferably 0.05<g, further preferably 0.10<g, further preferably 0.15<g, and preferably g<0.80, more preferably g<0.50, further preferably g<0.40, further preferably g<0.35, further preferably g<0.30, further preferably g<0.25. In this embodiment, the molar ratio of Eu, Sr, Ca, Al and Si in the molar ratio of each element contained in the phosphor powder can be determined, for example, by the following operation: dissolving the phosphor powder by a pressurized acid decomposition method, preparing a sample solution, and using the obtained sample solution as an object to perform quantitative analysis of the elements using an ICP emission spectrometer. In the present embodiment, the molar ratio of N and O in the molar ratio of each element contained in the phosphor powder can be determined by, for example, measuring 0.03 g of the phosphor powder and measuring the contents of oxygen and nitrogen using an oxygen and nitrogen analyzer. (Median particle size D 50 ) From the viewpoint of further improving the reliability of the phosphor powder, the median particle size D of the phosphor particles of this embodiment is 50 It is preferably 1 μm or more, more preferably 5 μm or more, further preferably 10 μm or more, further preferably 15 μm or more, further preferably 17 μm or more, further preferably 20 μm or more, and preferably 40 μm or less, more preferably 36 μm or less, further preferably 33 μm or less, further preferably 30 μm or less. In the application of converting blue light from a blue LED into red light, this degree of median particle size is preferred in terms of balancing various performances such as brightness, conversion efficiency, and reliability. In this embodiment, the median particle size D of the phosphor powder is 50 For example, it can be measured as a volume-based value by a laser diffraction scattering method. Median particle size D 50 The adjustment of can be carried out by appropriately adopting a known method such as pulverization and sieving. The details will be described later. (Absorption rate) From the viewpoint of further improving the reliability of the phosphor powder and the performance balance of the fluorescence characteristics, the absorptivity Z1 of the phosphor powder of this embodiment for light of a wavelength of 455 nm is preferably 90.0% or more, more preferably 92.0% or more, further preferably 94.0% or more, further preferably 95.0% or more, and preferably 99.9% or less, more preferably 99.0% or less, further preferably 98.0% or less. In the present embodiment, the absorption rate Z1 of the phosphor powder to light of a wavelength of 455 nm can be obtained by, for example, the following method. First, the fluorescent powder is filled in a concave cuvette in a manner that the surface becomes smooth, and is mounted in the opening of an integrating sphere. Next, a monochromatic light with a wavelength of 455 nm is introduced into the integrating sphere using an optical fiber from a Xe lamp as a light source as an excitation light for the fluorescent substance. The monochromatic light as the excitation light is irradiated on the fluorescent substance powder, and the fluorescence spectrum is measured using a spectrophotometer. The luminous intensity of the phosphor powder is determined from the data of the obtained fluorescence spectrum, and the number of excitation reflected light photons (Qref) and the number of fluorescence photons (Qem) are calculated. The number of excitation reflected light photons is calculated within the wavelength range of 450 to 465 nm, and the number of fluorescence photons is calculated within the range of 465 to 800 nm. In addition, using the same device, a standard reflector with a reflectivity of 99% (manufactured by Labsphere, Spectralon (registered trademark)) is installed at the opening of the integrating sphere, and the spectrum of the excitation light with a wavelength of 455 nm is measured. At this time, the number of excitation light photons (Qex) is calculated from the spectrum in the wavelength range of 450 to 465 nm. From the above calculation results, the absorption rate Z1 of the phosphor to the light of 455 nm was calculated based on the calculation formula shown below. Absorption rate of 455nm light Z1 = ((Qex-Qref) / Qex) × 100 (Internal Quantum Efficiency) From the viewpoint of further improving the reliability of the phosphor powder and the performance balance of the fluorescence characteristics, the internal quantum efficiency of the phosphor powder of this embodiment when excited by light of a wavelength of 455 nm is preferably 60.0% or more, more preferably 64.0% or more, further preferably 67.0% or more, further preferably 70.0% or more, and preferably 99.0% or less, more preferably 90.0% or less, further preferably 85.0% or less, further preferably 80.0% or less. In this embodiment, the internal quantum efficiency of the phosphor powder when excited by light of a wavelength of 455 nm can be calculated based on the calculation results of the number of excitation reflected light photons (Qref), the number of fluorescence photons (Qem) and the number of excitation light photons (Qex) according to the calculation formula shown below. Internal quantum efficiency = (Qem / (Qex-Qref))×100 (External quantum efficiency) From the viewpoint of further improving the reliability of the phosphor powder and the performance balance of the fluorescence characteristics, the external quantum efficiency of the phosphor powder of this embodiment when excited by light of a wavelength of 455 nm is preferably 60.0% or more, more preferably 63.0% or more, further preferably 66.0% or more, further preferably 68.0% or more, and preferably 99.0% or less, more preferably 90.0% or less, further preferably 85.0% or less, further preferably 80.0% or less. In this embodiment, the external quantum efficiency of the phosphor powder when excited by light of a wavelength of 455 nm can be calculated based on the calculation results of the number of excitation reflected light photons (Qref), the number of fluorescence photons (Qem) and the number of excitation light photons (Qex) according to the calculation formula shown below. External quantum efficiency = (Qem / Qex) × 100 In addition, based on the above formula, the relationship between the external quantum efficiency, the absorptivity for 455 nm light, and the internal quantum efficiency can be expressed as follows. External quantum efficiency = absorptivity of 455nm light × internal quantum efficiency (peak wavelength, half-peak width) From the viewpoint of further improving the reliability of the phosphor powder and the performance balance of the fluorescence characteristics, the peak wavelength of the fluorescence spectrum when the phosphor powder of this embodiment is irradiated with light of a wavelength of 455 nm is preferably 600 nm or more, more preferably 610 nm or more, further preferably 620 nm or more, further preferably 630 nm or more, further preferably 633 nm or more, and preferably 670 nm or less, more preferably 660 nm or less, further preferably 650 nm or less, further preferably 645 nm or less, further preferably 643 nm or less. Furthermore, from the viewpoint of further improving the reliability of the phosphor powder and the performance balance of the fluorescence characteristics, the half-width of the peak of the fluorescence spectrum is preferably greater than 70.0 nm, more preferably greater than 71.0 nm, further preferably greater than 72.0 nm, further preferably greater than 73.0 nm, and preferably less than 77.0 nm, more preferably less than 76.0 nm, further preferably less than 75.0 nm. In the present embodiment, the fluorescence spectrum when the phosphor powder is irradiated with light of a wavelength of 455 nm can be measured by, for example, the same method as the above-mentioned method for measuring the absorbance Z1. (Relative fluorescence intensity) From the viewpoint of further improving the reliability of the phosphor powder and the performance balance of the fluorescence characteristics, the relative fluorescence intensity Y1 of the phosphor powder of this embodiment is preferably 150% or more, more preferably 170% or more, more preferably 190% or more, more preferably 200% or more, more preferably 210% or more, more preferably 220% or more, and more preferably 225% or more. The upper limit of the relative fluorescence intensity Y1 is not particularly limited, and may be, for example, 400% or less, 350% or less, 300% or less, 280% or less, or 260% or less. In this embodiment, the relative fluorescence intensity Y1 of the phosphor powder can be obtained, for example, by the following operation: the peak intensity of the emission spectrum obtained by irradiating YAG:Ce with 455nm monochromatic light is set to 100%, and the peak intensity in the fluorescence spectrum measured by the same method as the measurement method of the above-mentioned absorbance Z1 is expressed as relative peak intensity (%). That is, the relative fluorescence intensity Y1 is a relative value relative to the standard sample. (Absorption rate after pressure cooker test) From the viewpoint of further improving the reliability of the phosphor powder, after maintaining 5 g of the phosphor powder of this embodiment in an atmosphere of 130°C, 98% relative humidity, and 0.16 MPaG for 53 hours using a pressure cooker testing machine, the absorptivity Z2 of the phosphor powder of this embodiment for light of a wavelength of 455 nm is preferably 92.0% or more, more preferably 93.0% or more, further preferably 94.0% or more, further preferably 94.5% or more, and preferably 99.9% or less, more preferably 99.0% or less, and further preferably 98.5% or less. In the present embodiment, the absorptivity Z2 of the phosphor powder with respect to light of a wavelength of 455 nm can be determined, for example, by the same method as the method for measuring the absorptivity Z1 described above. From the viewpoint of further improving the reliability of the phosphor powder, the absorption rate reduction rate (%) of the phosphor powder of this embodiment calculated by 100×(Z1-Z2) / Z1 is preferably greater than -5.0%, more preferably greater than -1.0%, further preferably greater than 0.0%, and is preferably less than 5.0%, more preferably less than 4.0%, further preferably less than 3.0%, further preferably less than 2.5%, and further preferably less than 2.0%. (Relative fluorescence intensity after pressure cooker test) When SCASN phosphor particles are included, from the viewpoint of further improving the reliability of the phosphor powder, after 5 g of the phosphor powder of this embodiment is maintained in an atmosphere of 130°C, 98% relative humidity, and 0.16 MPaG for 53 hours using a pressure cooker testing machine, the relative fluorescence intensity Y2 of the phosphor powder of this embodiment is preferably 221% or more, more preferably 223% or more, further preferably 225% or more, and preferably 400% or less, more preferably 300% or less, and further preferably 260% or less. In addition, when CASN phosphor particles are included, from the viewpoint of further improving the reliability of the phosphor powder, the relative fluorescence intensity Y2 of the phosphor powder of this embodiment is preferably 130% or more, more preferably 150% or more, further preferably 170% or more, further preferably 190% or more, further preferably 200% or more, further preferably 210% or more, further preferably 220% or more, and preferably 400% or less, more preferably 300% or less, further preferably 260% or less. From the viewpoint of further improving the reliability of the phosphor powder, the relative fluorescence intensity reduction rate (%) of the phosphor powder of this embodiment calculated by 100×(Y1-Y2) / Y1 is preferably greater than -5.0%, more preferably greater than -1.0%, further preferably greater than 0.0%, and preferably less than 10.0%, more preferably less than 8.0%, further preferably less than 6.0%, and further preferably less than 5.0%. <Method for producing phosphor powder> The phosphor powder of this embodiment can be obtained by appropriately selecting the selection of raw materials, the usage ratio of each raw material, the manufacturing steps and manufacturing conditions, etc. Specifically, the phosphor powder of this embodiment can be preferably manufactured through the following steps: A mixing step of mixing the starting materials to obtain a raw material mixed powder, · Calcination step: calcining the raw material mixed powder to obtain a block of calcined powder, ·Powdering process: Powdering the calcined powder in bulk. Annealing step: heat-treating the calcined powder to obtain annealed powder. Acid treatment step: treating the annealed powder with acid to obtain acid-treated powder. an elutriation step to remove fine particles from the acid treated powder, and An atmospheric heat treatment step of subjecting the acid-treated powder to an atmospheric heat treatment to obtain an atmospheric heat-treated powder. In addition, additional steps other than these steps may be performed when producing the phosphor powder. (Mixing process) In the mixing step of the present embodiment, starting materials are mixed to prepare a raw material mixed powder. From the viewpoint of further improving the fluorescence characteristics of the phosphor powder, the starting raw materials of this embodiment preferably all contain europium compounds, strontium compounds, calcium compounds, silicon nitride and aluminum nitride, and more preferably all contain europium oxide, strontium nitride, calcium nitride, silicon nitride and aluminum nitride. The form of each starting material in the present embodiment is preferably powder. From the viewpoint of further improving the fluorescence characteristics of the phosphor powder, the europium compound of the present embodiment preferably contains one selected from europium oxide, europium nitride, and europium fluoride alone, and more preferably contains europium oxide alone. In the calcination process of the present embodiment, europium can be divided into solid-dissolved europium, volatilized europium and europium remaining as a heterogeneous component. The heterogeneous component containing europium can be removed by acid treatment or the like. However, when too many heterogeneous components containing europium are generated, components insoluble in acid treatment are generated, and brightness is reduced. In addition, if it is a heterogeneous phase that does not absorb excess light, it can be in a residual state, or europium can be contained in the heterogeneous phase. From the viewpoint of further improving the fluorescence characteristics of the phosphor powder, the amount of the europium compound in this embodiment is preferably used in an amount such that a in the above general formula in the feed ratio is preferably 0.05<a<0.15, and more preferably 0.07<a<0.10. Incidentally, when the core particles described later are used, a in the above inequality does not include the amount of europium in the core particles. On the other hand, from the viewpoint of further improving the fluorescent properties of the phosphor powder, the amount of the strontium compound in this embodiment is preferably used in an amount such that b in the above general formula in the feed ratio is preferably 0.85<b<1.00, and more preferably 0.95<b<0.98. Furthermore, when the core particles described later are used, b in the above inequality does not include the amount of strontium in the core particles. The starting material (raw material mixed powder) of this embodiment preferably contains SCASN phosphor core particles having a median particle size of 10 μm to 20 μm. In other words, a part of the starting material preferably contains SCASN phosphor core particles having a median particle size of 10 μm to 20 μm. From the viewpoint of further improving the fluorescence characteristics of the phosphor powder, the median particle size of the SCASN phosphor core particles of this embodiment is preferably 10 μm or more, more preferably 15 μm or more, and is preferably 20 μm or less, more preferably 17 μm or less. In this specification, the SCASN phosphor core particle is also simply referred to as "core particle", "core" or the like. Although the detailed reason is not clear, it is believed that by using the core particles, crystallization is carried out from the core particles as the starting point in the subsequent calcination process. Therefore, the way of crystal growth is changed compared with the case where the calcination process is carried out without using the core particles (for example, by using the core, the composition of each particle is easily consistent compared with the case where the core is not used). Furthermore, as a result, it should be easy to obtain a phosphor powder with improved fluorescence characteristics. As an example, the core particles of this embodiment may be phosphor powders represented by the same general formula as the phosphor powders of this embodiment described above. In other words, as an example, the color difference ΔE before and after the pressure cooker test of the core particles is * It is not necessarily 25.0 or less, but the composition is the same as or similar to that of the phosphor powder of this embodiment. When core particles are used, their amount is preferably 7 mass % or more, more preferably 9 mass % or more, and preferably 13 mass % or less, more preferably 11 mass % or less, in the total amount of the raw material mixed powder, from the viewpoint of further improving the fluorescence characteristics of the phosphor powder. The core particles can be obtained, for example, by undergoing almost the same process as the phosphor powder of the present embodiment. That is, in the manufacturing process of the phosphor powder of the present embodiment, the core particles are not added in the mixing process, and other than that, the core particles can be obtained in the same manner. The composition (general formula) of the core particles is also preferably the same as that of the phosphor powder of the present embodiment. In the mixing step of the present embodiment, the raw material mixed powder can be obtained by, for example, a method of dry mixing the starting materials, a method of wet mixing in an inert solvent that does not substantially react with each starting material, and then removing the solvent, etc. As a mixing device, for example, a small pulverizing mixer, a V-type mixer, a swing mixer, a ball mill, a vibration mill, etc. can be used. After mixing using the device, the aggregates can be removed by a sieve as needed, thereby obtaining the raw material mixed powder. In order to suppress the degradation of the starting materials and the unintentional incorporation of oxygen, the mixing step of the present embodiment is preferably performed under a nitrogen atmosphere or an environment with as little water (humidity) as possible. (Calcination process) In the calcining step of the present embodiment, the raw material mixed powder obtained in the mixing step is calcined to obtain calcined powder. From the viewpoint of further improving the reliability of the phosphor powder and the performance balance of the fluorescence characteristics, the calcination temperature in the calcination process of the present embodiment is preferably 1850°C or more, more preferably 1900°C or more, and preferably 2050°C or less, more preferably 2000°C or less. When the calcination temperature is above the above lower limit, the grain growth of the phosphor particles is more effectively performed. Therefore, the reliability of the phosphor powder and the performance balance of the fluorescence characteristics can be further improved. When the calcination temperature is below the above upper limit, the decomposition of the phosphor particles can be further suppressed. Therefore, the reliability of the phosphor powder and the performance balance of the fluorescence characteristics can be further improved. From the viewpoint of further improving the reliability of the phosphor powder and the performance balance of the fluorescence characteristics, the heating holding time in the calcination step of this embodiment is preferably 5 hours or more, more preferably 7 hours or more, and preferably 15 hours or less, more preferably 10 hours or less. From the viewpoint of further improving the reliability of the phosphor powder and the performance balance of the fluorescence characteristics, the pressure in the calcination step of the present embodiment is preferably 0.7 MPaG or more, more preferably 0.8 MPaG or more, and is preferably 1 MPaG or less, more preferably 0.9 MPaG or less. The calcination step of the present embodiment is preferably performed in a nitrogen atmosphere from the viewpoint of controlling the oxygen concentration, etc. That is, the calcination step is preferably performed in a nitrogen atmosphere at a pressure of 0.7 MPaG to 1 MPaG. In the calcination process of this embodiment, from the viewpoint of further improving the reliability of the phosphor powder and the performance balance of the fluorescence characteristics, it is preferred to fill the mixture into a container that is not easy to react with the raw material mixed powder during calcination and heat it. Specifically, it is preferred to use a high melting point container, and more preferably a tungsten container. This can suppress the generation of heterogeneous phases. In addition, in the calcination process of this embodiment, from the viewpoint of further improving the reliability of the phosphor powder and the performance balance of the fluorescence characteristics, the container is preferably a sealed container with high airtightness. By calcining the raw material mixed powder under a sealed condition, it is possible to prevent oxygen and water (humidity) from invading the interior of the container, suppressing the degradation of the raw material mixed powder, etc., thereby further improving the reliability of the phosphor powder and the performance balance of the fluorescence characteristics. The structure of the sealed container is preferably a structure in which the inside of the container is sealed by narrowing the gap between the lid and the main body of the container. As a method for narrowing the gap between the lid and the main body of the sealed container, for example, the following method can be cited: when the existing container is a structure in which only the lid is placed on the main body, a structure in which the main body and the lid of the container are interlocked is adopted. (Powdering process) In the pulverization step of the present embodiment, the calcined powder is temporarily pulverized by using a single or combined treatment such as disintegration, pulverization, and classification. The calcined powder obtained through the calcination step is generally a massive sintered body, so pulverizing the calcined powder facilitates handling. As a specific processing method of the pulverization step of this embodiment, for example, a method of pulverizing the sintered body into a predetermined particle size using a general pulverizer such as a ball mill, a vibration mill, or a jet mill can be cited. However, excessive pulverization may sometimes generate fine particles that easily scatter light or may sometimes cause crystal defects on the particle surface, resulting in a decrease in luminous efficiency, so it is necessary to be careful. (Annealing process) In the annealing step of the present embodiment, after the pulverizing step, the calcined powder may be annealed at a temperature lower than the calcination temperature in the calcination step to obtain the annealed powder. This can sufficiently improve the luminous efficiency of the phosphor powder. In addition, since strains and defects are removed by rearrangement of elements, the reliability of the phosphor powder and the performance balance of the fluorescence characteristics can be improved. On the other hand, a different phase may be generated in the annealing step, but this can be sufficiently removed by the acid treatment step described later. From the viewpoint of further improving the reliability of the phosphor powder and the performance balance of the fluorescence characteristics, the annealing step of the present embodiment is preferably performed in a hydrogen atmosphere or an argon atmosphere, and more preferably in an argon atmosphere. From the viewpoint of further improving the reliability of the phosphor powder and the performance balance of the fluorescence characteristics, the pressure in the annealing step of this embodiment is preferably 0.7 MPaG or more, more preferably 0.8 MPaG or more, and is preferably 1 MPaG or less, more preferably 0.9 MPaG or less. From the viewpoint of further improving the reliability of the phosphor powder and the performance balance of the fluorescence characteristics, the heat treatment temperature in the annealing step of this embodiment is preferably 1250°C or higher, more preferably 1300°C or higher, and preferably 1450°C or lower, more preferably 1400°C or lower. From the viewpoint of further improving the reliability of the phosphor powder and the performance balance of the fluorescence characteristics, the heat treatment time in the annealing step of this embodiment is preferably 5 hours or more, more preferably 7 hours or more, and preferably 10 hours or less, more preferably 9 hours or less. In the annealing step of the present embodiment, the mixture is preferably filled into a container that does not easily react with the calcined powder during heat treatment, for example, a high melting point container, specifically a container having an inner wall made of tungsten, and heated, similarly to the calcining step. In addition, from the viewpoint of further improving the reliability of the phosphor powder and the performance balance of the fluorescence characteristics, the container used in the annealing step is preferably a sealed container as described above, and more preferably, the containers used in both the calcining step and the annealing step are sealed containers. (Acid treatment process) In the acid treatment step of the present embodiment, the annealed powder obtained in the annealing step is subjected to an acid treatment to obtain an acid-treated powder. This can remove at least a portion of impurities that do not contribute to light emission. It is presumed that impurities that do not contribute to light emission are generated during the calcination step and the annealing step. In the acid treatment step of this embodiment, as the acid, an aqueous solution containing one or more acids selected from hydrofluoric acid, sulfuric acid, phosphoric acid, hydrochloric acid, and nitric acid can be used. In particular, from the viewpoint of further improving the reliability of the phosphor powder and the performance balance of the fluorescence characteristics, the aqueous solution preferably contains hydrochloric acid, hydrofluoric acid, nitric acid, and a mixed acid of hydrofluoric acid and nitric acid, and more preferably contains hydrochloric acid. The acid treatment process of this embodiment can be performed by dispersing the annealed powder in an aqueous solution containing the above-mentioned acid. From the viewpoint of further improving the reliability of the phosphor powder and the performance balance of the fluorescence characteristics, the stirring time is preferably 30 minutes or more, more preferably 45 minutes or more, and preferably 3 hours or less, more preferably 2 hours or less. In addition, from the viewpoint of further improving the reliability of the phosphor powder and the performance balance of the fluorescence characteristics, the temperature during stirring is preferably 50°C or more, more preferably 60°C or more, and preferably 100°C or less, more preferably 90°C or less. After the acid treatment process of this embodiment, the liquid in which the annealing powder is dispersed may be boiled, or substances other than the phosphor powder may be separated by filtration, and substances attached to the phosphor particles may be washed with water as needed. After washing with water, the phosphor powder is usually dried by natural drying or drying in a dryer. The dried phosphor powder may be placed in a crucible and heated for surface modification. (Elutriation process) In the elutriation step of this embodiment, fine particles are removed from the acid-treated powder by elutriation after the acid treatment step, thereby removing fine particles that reduce the fluorescence characteristics of the phosphor powder, and further improving the reliability of the phosphor powder and the performance balance of the fluorescence characteristics. The elutriation step is performed by the following operations: the acid-treated powder is put into a dispersion medium, a dispersion is prepared and stirred, and then the acid-treated powder in the dispersion is precipitated and the supernatant is removed. After the supernatant is removed, the precipitate is collected by filtration and dried, thereby obtaining the acid-treated powder from which the fine particles have been removed. In the elutriation step, the preparation of the dispersion and the removal of the supernatant can be repeated. As the dispersion medium, from the viewpoint of further improving the reliability of the phosphor powder and the performance balance of the fluorescence characteristics, it is preferred to use an aqueous solution of sodium hexametaphosphate. (Atmospheric heating treatment process) In the atmospheric heat treatment step of the present embodiment, after the elutriation step, the acid-treated powder is subjected to atmospheric heat treatment to obtain atmospheric heat-treated powder. As a result, the reliability of the phosphor powder and the performance balance of the fluorescence characteristics are improved. On the other hand, excessive atmospheric heating treatment will reduce the fluorescence characteristics of the phosphor powder, so it is important to perform atmospheric heating treatment under appropriate conditions to improve the reliability of the phosphor powder and the performance balance of the fluorescence characteristics. From the viewpoint of further improving the reliability of the phosphor powder and the performance balance of the fluorescence characteristics, the atmospheric heat treatment step of the present embodiment is preferably performed under atmospheric pressure in the atmosphere. From the viewpoint of further improving the performance balance between the reliability and fluorescence characteristics of the phosphor powder, the heat treatment temperature in the atmospheric heat treatment step of the present embodiment is preferably 250° C. or higher, more preferably 280° C. or higher, more preferably 320° C. or higher, more preferably 350° C. or higher, more preferably 380° C. or higher, and preferably 450° C. or lower, more preferably 420° C. or lower. When the heat treatment temperature is at least the lower limit, the reliability of the phosphor powder can be further improved, and when the heat treatment temperature is at most the upper limit, the reduction in the fluorescence characteristics of the phosphor powder can be suppressed. From the viewpoint of further improving the reliability of the phosphor powder and the performance balance of the fluorescence characteristics, the heat treatment time in the atmospheric heat treatment step of the present embodiment is preferably 0.5 hours or more, more preferably 2 hours or more, more preferably 3.5 hours or more, and preferably 6 hours or less, more preferably 5 hours or less. When the heat treatment time is greater than the lower limit, the reliability of the phosphor powder can be further improved, and when the heat treatment time is less than the upper limit, the reduction in the fluorescence characteristics of the phosphor powder can be suppressed. From the viewpoint of further improving the reliability of the phosphor powder and the performance balance of the fluorescence characteristics, the heating rate in the atmospheric heating treatment process of the present embodiment is preferably 1°C / minute or more, more preferably 2°C / minute or more, and preferably 10°C / minute or less, more preferably 5°C / minute or less, and even more preferably 3°C / minute or less. <Complex> The composite body of the present embodiment includes, for example, the above-mentioned phosphor powder and a sealing material that seals the phosphor powder. In the composite body of the present embodiment, the above-mentioned phosphor powder is dispersed in the sealing material. From the viewpoint of further improving the reliability of the composite, the sealing material of the present embodiment preferably includes one or more selected from silicone resin, epoxy resin, urethane resin, glass, and ceramic. When the total amount of the composite is set to 100 mass%, from the viewpoint of further improving the reliability of the composite, the content of the phosphor powder in this embodiment is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, further preferably 1 mass% or more, and preferably 20 mass% or less, more preferably 15 mass% or less, further preferably 10 mass% or less, further preferably 5 mass% or less. The composite of the present embodiment may be produced by adding the phosphor powder of the present embodiment to a liquid resin, glass, ceramic or the like, uniformly mixing the mixture, and then curing or sintering the mixture by heat treatment. <Light-emitting device> The light-emitting device of this embodiment includes a light-emitting element that emits excitation light and a complex of this embodiment that converts the wavelength of the excitation light. Hereinafter, a schematic cross-sectional view schematically showing an example of the structure of the light emitting device of this embodiment will be used. Figure 1 The light emitting device of this embodiment is described below. Figure 1 As shown, the light emitting device 100 includes a light emitting element 120 , a heat sink 130 , a housing 140 , a first lead frame 150 , a second lead frame 160 , bonding wires 170 , 172 , and a composite body 40 . The light emitting element 120 is mounted on a predetermined area of ​​the upper surface of the heat sink 130. By mounting the light emitting element 120 on the heat sink 130, the heat dissipation of the light emitting element 120 can be improved. In addition, a package substrate may be used instead of the heat sink 130. The light emitting element 120 is a semiconductor element that emits excitation light. As the light emitting element 120, for example, an LED chip that generates light with a wavelength of 300nm to 500nm corresponding to near ultraviolet to blue light can be used. An electrode (not shown) disposed on the upper surface side of the light emitting element 120 is connected to the surface of the first lead frame 150 via a bonding wire 170 such as a metal wire. In addition, another electrode (not shown) formed on the upper surface of the light emitting element 120 is connected to the surface of the second lead frame 160 via a bonding wire 172 such as a metal wire. The housing 140 is formed with a substantially funnel-shaped recessed portion whose aperture gradually expands from the bottom surface toward the top. The light emitting element 120 is disposed on the bottom surface of the recessed portion. The wall surface of the recessed portion surrounding the light emitting element 120 functions as a reflector. The composite 40 is filled in the above-mentioned recessed portion whose wall is formed by the shell 140. The composite 40 is a wavelength conversion component that converts the excitation light emitted by the light-emitting element 120 into light of a longer wavelength. As the composite 40, the composite of the present embodiment is used, and the above-mentioned phosphor powder 1 is dispersed in a sealing material 30 such as a resin. The light-emitting device 100 generates a mixed color of the light of the light-emitting element 120 and the light generated by the phosphor powder 1 that absorbs the light of the light-emitting element 120 and is excited. It should be noted that in order to obtain white as a mixed color (in order to make the light-emitting device 100 a white LED), it is preferred that the composite 40 contains, for example, LuAG phosphor powder in addition to the phosphor powder 1 (it is preferred that LuAG phosphor powder is dispersed in the sealing material 30 in addition to the phosphor powder 1). In the present embodiment, good white light can be easily obtained when the peak wavelength and half-peak width of the fluorescence spectrum of the phosphor powder 1 are within a certain numerical range. and, Figure 1 Although a surface-mounted light emitting device is exemplified in the above, the light emitting device is not limited to the surface-mounted type. The light emitting device may also be a bullet type, a COB (chip on board) type, a CSP (chip scale package) type, or the like. Although the embodiments of the present invention have been described above, these are examples of the present invention, and various configurations other than the above can be adopted. In addition, the present invention is not limited to the above embodiments, and modifications and improvements within the scope of achieving the purpose of the present invention are included in the present invention. Example The embodiments of the present invention will be described in detail based on Examples and Comparative Examples. However, the present invention is not limited to the Examples. (Example 1) <Preparation of core agent> First, put 60.61 g of α-type silicon nitride (Si3N4, manufactured by Ube Industries, Ltd., SN-E10 grade), 53.13 g of aluminum nitride (AlN, manufactured by Tokuyama Co., Ltd., E grade) and 13.68 g of europium oxide (Eu2O3, manufactured by Shin-Etsu Chemical Co., Ltd.) into a container and pre-mix them. Next, in a glove box maintained in a nitrogen atmosphere in which the moisture content was adjusted to less than 1 mass ppm and the oxygen concentration was adjusted to less than 50 mass ppm, 5.76 g of calcium nitride (Ca3N2, manufactured by Materion Corporation) and 106.82 g of strontium nitride (Sr3N2, manufactured by Kojun Chemical Research Institute Co., Ltd., purity 2N) were further added to the above container and dry mixed to obtain a mixture. 240 g of the above mixture was filled into a sealed container made of tungsten in a glove box. After closing the lid of the sealed container, it was taken out of the glove box and placed in an electric furnace equipped with a carbon heater. Then, vacuum exhaust was performed until the pressure in the electric furnace reached 0.1 PaG or less. Here, the sealed container has a structure in which the main body and the lid are interlocked with each other, and the gap between the lid and the main body is narrower than that of the existing container, thereby improving the sealing performance. Under the state of continuous vacuum exhaust, the temperature in the electric furnace is raised to 600°C. After reaching 600°C, nitrogen is introduced into the electric furnace and the pressure in the electric furnace is adjusted to 0.85MPaG. Then, the temperature in the electric furnace is raised to 1950°C under a nitrogen atmosphere, and heat treatment is carried out for 8 hours after reaching 1950°C. Then, the heating is terminated and cooled to room temperature. After cooling to room temperature, red lumps are recovered from the container. The recovered lumps are crushed and sieved in a mortar to prepare core particles (core agent) with a median particle size of 16μm. <Manufacturing of phosphor powder> 51.50 g of α-type silicon nitride (Si3N4, manufactured by Ube Industries, Ltd., SN-E10 grade), 45.14 g of aluminum nitride (AlN, manufactured by Tokuyama Co., Ltd., E grade), 15.50 g of europium oxide (Eu2O3, manufactured by Shin-Etsu Chemical Co., Ltd.) and 24.00 g of the nucleating agent prepared as described above are measured into a container and pre-mixed. Next, in a glove box with a nitrogen atmosphere in which the water content is adjusted to less than 1 mass ppm and the oxygen concentration is adjusted to less than 50 mass ppm, 0.27 g of calcium nitride (Ca3N2, manufactured by Materion) and 103.58 g of strontium nitride (Sr3N2, manufactured by Kojun Chemical Research Institute, purity 2N) are further measured into the above container and dry mixed. A mixed powder is thus obtained. The relationship between the feeding amount of the nucleating agent and the raw material powder (mass %) and the details of the feeding amount of each element in the raw material powder (mol ratio) are shown in Table 1. 240 g of the mixed powder was filled into a sealed container made of tungsten in a glove box. After closing the lid of the sealed container, it was taken out of the glove box and placed in an electric furnace equipped with a carbon heater. Then, the electric furnace was fully evacuated until the pressure in the electric furnace reached 0.1 PaG or less. Under the condition of continuous vacuum exhaust, the temperature in the electric furnace is raised to 600°C. After reaching 600°C, nitrogen is introduced into the electric furnace and the pressure in the electric furnace is adjusted to 0.85MPaG. Then, the temperature in the electric furnace is raised to 1950°C under a nitrogen atmosphere, and after reaching 1950°C, a heat treatment is performed for 8 hours. Then, the heating is terminated and the furnace is cooled to room temperature. After cooling to room temperature, a red mass is recovered from the container. The recovered mass is crushed, sieved, and the particle size is adjusted to obtain a calcined powder. The obtained calcined powder is filled into a sealed container made of tungsten, quickly moved to an electric furnace equipped with a carbon heater, and fully evacuated until the pressure in the furnace reaches below 0.1 PaG. Heating is started while continuing to evacuate the vacuum. When the temperature reaches 600°C, argon gas is introduced into the furnace to adjust the pressure of the furnace atmosphere to atmospheric pressure. After the introduction of argon gas, the temperature continues to rise to 1350°C. After the temperature reaches 1350°C, heating treatment is carried out for 8 hours. Then, heating is terminated and cooled to room temperature. After cooling to room temperature, the annealed powder is recovered from the container. The recovered powder is sieved to adjust the particle size. Thus, annealed powder is obtained. The obtained annealed powder is put into 2.0M hydrochloric acid at room temperature to make the slurry concentration be 25 mass % and immersed for 1 hour at 70-80°C. Thus, the acid treatment is carried out. After the acid treatment, the hydrochloric acid slurry is boiled for 1 hour while stirring. The slurry after the boiling treatment is cooled to room temperature and filtered, and the acid-treated liquid is separated from the solid component to obtain an acid-treated product. The acid-treated product is placed in a dryer set at a temperature in the range of 100-120°C for 12 hours and dried to obtain an acid-treated powder. The obtained acid-treated powder was added to an aqueous sodium hexametaphosphate solution to prepare a dispersion and stirred, and then the acid-treated powder in the dispersion was precipitated and the supernatant was removed. After the supernatant was removed, the precipitate was collected by filtration and dried to obtain an acid-treated powder from which fine particles were removed. The preparation of the dispersion and the removal of the supernatant were repeated 5 times. Next, the obtained acid-treated powder was filled into an alumina crucible, and quickly moved into an electric furnace equipped with a carbon heater, and heated at a heating rate of 2.5°C / min under atmospheric pressure until the temperature reached 300°C. Next, after the temperature reached 300°C, atmospheric heating treatment was performed for 1 hour. Then, the heating was terminated, and the mixture was cooled to room temperature to obtain atmospheric heating-treated powder. Through the above operations, the phosphor powder of Example 1 was obtained. The obtained phosphor sample was subjected to powder X-ray diffraction using CuKα radiation using an X-ray diffraction device (Ultima IV manufactured by Rigaku Corporation). It was confirmed that the obtained X-ray diffraction pattern was the same as that of CaAlSiN3 crystal, and the main crystalline phase had the same crystal structure as that of CaAlSiN3 crystal. (Example 2) The phosphor powder of Example 2 was obtained in the same manner as in Example 1 except that the treatment temperature for the atmospheric heat treatment was 400°C. (Example 3) The phosphor powder of Example 3 was obtained in the same manner as in Example 1 except that the treatment time for the atmospheric heat treatment was changed to 4 hours. (Example 4) The phosphor powder of Example 4 was obtained in the same manner as in Example 1 except that the treatment temperature in the atmosphere heat treatment was 400° C. and the treatment time was 4 hours. (Comparative Example 1) The phosphor powder of Comparative Example 1 was obtained in the same manner as in Example 1 except that the atmospheric heating treatment was not performed. (Comparative Example 2) The phosphor powder of Comparative Example 2 was obtained in the same manner as in Example 1 except that the treatment temperature of the atmospheric heat treatment was set to 200°C. (Comparative Example 3) The phosphor powder of Comparative Example 3 was obtained in the same manner as in Example 1 except that a non-sealed container made of tungsten was used instead of a sealed container made of tungsten as the container used for calcination and annealing. Here, the non-sealed container refers to a container having a structure in which only a cover is placed on a main body. <Color difference ΔE * > First, the CIE 1976 L spectra of the phosphor powder were measured using a colorimeter (ZE6000, manufactured by Nippon Denshoku Industries Co., Ltd.) under the conditions of light source C and a 2° viewing field. * a * b * The chromaticity coordinates (L1 * 、a1 * 、b1* ). Then, the CIE1976L value of the phosphor powder was measured in the same manner after a pressure cooker test was performed using a pressure cooker tester (manufactured by ESPEC CORP., EHS-221M) in which 5 g of the phosphor powder was exposed to an atmosphere of 130°C, 98% relative humidity, and 0.16 MPa for 53 hours. * a * b * The chromaticity coordinates specified in the color system (L2 * 、a2 * 、b2 * ). Then, (L1 * -L2 * ) 2 、(a1 * -a2 * ) 2 and (b1 * -b2 * ) 2 Then, ΔE is calculated by the following formula: * The results are shown in Table 2. E * ={(L1 * -L2 * ) 2 +(a1 * -a2 * ) 2 +(b1 * -b2 * ) 2} 1 / 2 <Composition> First, the phosphor powder was dissolved by pressurized acid decomposition to prepare a sample solution. Next, the obtained sample solution was used as an object to perform quantitative element analysis using an ICP emission spectrometer (manufactured by Shimadzu Corporation, ICPE-9000) to measure the molar ratio of Eu, Sr, Ca, Al and Si contained in the phosphor powder. The results are shown in Table 1. Furthermore, 0.03 g of the phosphor powder was weighed and the contents of oxygen and nitrogen were measured using an oxygen and nitrogen analyzer to determine the molar ratio of N to O. The results are shown in Table 1. <Median particle size> Microtrac MT3300EX II (manufactured by Microtrac BEL) was used to measure the particle size distribution of the phosphor powder using the laser diffraction scattering method in accordance with JIS R1629:1997. Specifically, about 0.1 g of phosphor powder was added to 100 mL of ion exchange water, and dispersed for 3 minutes using Ultrasonic Homogenizer US-150E (manufactured by Nippon Seiki Seisaku-sho Co., Ltd., chip size φ20 mm, Amplitude 100%, oscillation frequency 19.5 KHz, amplitude about 31 μm), and then measured using MT3300EX II. The median particle size D of the phosphor powder was calculated from the obtained particle size distribution. 50 The results are shown in Table 2. <Fluorescence spectrum> Fluorescence measurement was performed using a spectrofluorophotometer (F-7000, manufactured by Hitachi High-Technologies Corporation) calibrated with rhodamine B and a sub-standard light source. Specifically, first, the phosphor powder is filled in a concave cuvette in a manner that the surface becomes smooth, and the cuvette is mounted in the opening of an integrating sphere. Next, a monochromatic light with a wavelength of 455 nm is introduced into the integrating sphere using an optical fiber from a Xe lamp as a light source as an excitation light for the phosphor. The monochromatic light as the excitation light is irradiated on the phosphor powder, and the fluorescence spectrum is measured using a spectrophotometer. <Peak wavelength, half-peak width, relative fluorescence intensity> The peak wavelength and half-peak width of the fluorescence spectrum were determined from the fluorescence spectrum when the obtained phosphor powder was irradiated with light of wavelength 455 nm. The relative fluorescence intensity Y1 of the phosphor powder was also determined from the peak intensity. The results are shown in Table 2. Here, the relative fluorescence intensity Y1 is obtained by setting the peak height of the emission spectrum obtained by irradiating YAG:Ce (manufactured by Kasei Optronics Co., Ltd., P46Y3) with 455nm monochromatic light as 100% and expressing the peak intensity of the fluorescence spectrum as relative peak intensity (%). That is, the relative fluorescence intensity Y1 is a relative value relative to the standard sample. <Absorption rate, internal quantum efficiency, external quantum efficiency> The luminous intensity of the phosphor powder is determined from the data of the obtained fluorescence spectrum, and the number of excitation reflected light photons (Qref) and the number of fluorescence photons (Qem) are calculated. The number of excitation reflected light photons is calculated within the wavelength range of 450 to 465 nm, and the number of fluorescence photons is calculated within the range of 465 to 800 nm. In addition, using the same device, a standard reflector with a reflectivity of 99% (manufactured by Labsphere, Spectralon (registered trademark)) is installed at the opening of the integrating sphere, and the spectrum of the excitation light with a wavelength of 455 nm is measured. At this time, the number of excitation light photons (Qex) is calculated from the spectrum in the wavelength range of 450 to 465 nm. From the above calculation results, the absorptivity Z1 of the phosphor powder for light of 455 nm, the internal quantum efficiency, and the external quantum efficiency were determined based on the following calculation formula. Absorption rate of 455nm light Z1 = ((Qex-Qref) / Qex) × 100 Internal quantum efficiency = (Qem / (Qex-Qref))×100 External quantum efficiency = (Qem / Qex) × 100 <Relative fluorescence intensity reduction rate> The relative fluorescence intensity Y2 (%) of the phosphor powder was measured in the same manner as Y1 above, after 5 g of the phosphor powder was kept in an atmosphere of 130°C, 98% relative humidity, and 0.16 MPaG for 53 hours using a pressure cooker tester (manufactured by ESPEC CORP.). The relative fluorescence intensity reduction rate (%) of the phosphor powder before and after the pressure cooker test was calculated from the above measured values ​​by 100×(Y1-Y2) / Y1. The results are shown in Table 2. <Absorption rate reduction rate> The absorptivity Z2 (%) of the phosphor powder to 455 nm light was measured by the same method as Z1 above, using a pressure cooker tester (EHS-221M manufactured by ESPEC CORP.) after 5 g of the phosphor powder was kept at 130°C, 98% relative humidity, and 0.16 MPaG for 53 hours. From the above measured values, the absorptivity reduction rate (%) of the phosphor powder before and after the pressure cooker test was calculated by 100×(Z1-Z2) / Z1. The results are shown in Table 2. The feed ratio of raw materials is shown in Table 1. In Table 1, the values ​​in the columns of Eu (mol ratio), Sr (mol ratio), Ca (mol ratio), Al (mol ratio), Si (mol ratio), and b / (b+c) do not include the elements in the core particles. Color difference ΔE before and after pressure cooker test* The relative fluorescence intensity reduction rate of the phosphor powders of Examples 1 to 4, which was 25.0 or less, was 3.7% or less, and the absorption rate reduction rate was 1.6% or less. On the other hand, the color difference ΔE before and after the pressure cooker test * The phosphor powders of Comparative Examples 1 and 2 exceeding 25.0 had a relative fluorescence intensity reduction rate of 10.5% or more and an absorptivity reduction rate of 5.2% or more. From this, it can be understood that the phosphor powders of Examples 1 to 4 have improved reliability compared to the phosphor powders of Comparative Examples 1 to 3. This application claims the benefit of priority based on Japanese patent application No. 2023-118485, filed on July 20, 2023, and all the contents disclosed therein are incorporated herein by reference in their entirety.

Claims

1. A phosphor powder comprising one or more phosphor particles selected from CASN phosphor particles and SCASN phosphor particles, When a pressure cooker test was conducted by exposing 5 g of the phosphor powder to an atmosphere of 130° C., 98% relative humidity, and 0.16 MPa for 53 hours using a pressure cooker tester, CIE1976L * a * b * The chromaticity coordinates (L1 * 、a1 * 、b1 * ) and the chromaticity coordinates (L2 * 、a2 * 、b2 * ) color difference ΔE * ={(L1 * -L2 * ) 2 +(a1 * -a2 * ) 2 +(b1 * -b2 * ) 2 } 1 / 2 Below 25.

0.

2. The phosphor powder according to claim 1, wherein The (L1 * -L2 * ) 2 Below 65.

0.

3. The phosphor powder according to claim 1 or 2, wherein The (a1 * -a2 * ) 2 Below 260.

0.

4. The phosphor powder according to any one of claims 1 to 3, wherein The (b1 * -b2 * ) 2 Below 300.

0.

5. The phosphor powder according to any one of claims 1 to 4, wherein Contains the general formula Eu a Sr b Ca c Al d Si e N f O g It represents phosphor particles with 0<a<1.00, 0<b<1.00, 0<c<1.00, 0.70<a+b+c<1.30, 0.70<d<1.30, 0.70<e<1.30, 0<f<3.00, 0<g<3.00, and 2.50<f+g<3.

50.

6. The phosphor powder according to claim 5, wherein a<0.30。 7. The phosphor powder according to claim 5 or 6, wherein b>0.50。 8. The phosphor powder according to any one of claims 5 to 7, wherein The molar ratio of b / (b+c) of the phosphor powder is 0.96 to 0.

99.

9. The phosphor powder according to any one of claims 1 to 8, wherein The volume-based median particle size D of the phosphor powder based on the laser diffraction scattering method is 50 1μm~40μm.

10. The phosphor powder according to any one of claims 1 to 9, wherein The relative fluorescence intensity reduction rate of the phosphor powder according to the following method 2 is 10.0% or less, Method 2: When the relative fluorescence intensity of the phosphor powder measured by a spectrophotometer is set to Y1, and the relative fluorescence intensity of the phosphor powder after 5 g of the phosphor powder is kept in an atmosphere of 130°C, 98% relative humidity, and 0.16 MPaG for 53 hours using a pressure cooker testing machine is set to Y2, 100×(Y1-Y2) / Y1 is set to the relative fluorescence intensity reduction rate, and the units of Y1, Y2 and relative fluorescence intensity reduction rate are %.

11. The phosphor powder according to claim 10, wherein The Y1 is 150% or more.

12. The phosphor powder according to any one of claims 1 to 11, wherein The reduction rate of the absorptivity of the phosphor powder to light of wavelength 455 nm based on the following method 3 is 5.0% or less, Method 3: Let the absorptivity of the phosphor powder to light of wavelength 455 nm measured by a spectrophotometer be Z1, let the absorptivity of the phosphor powder to light of wavelength 455 nm after keeping 5 g of the phosphor powder at 130°C, 98% relative humidity, and 0.16 MPaG for 53 hours using a pressure cooker testing machine be Z2, let 100×(Z1-Z2) / Z1 be the absorptivity reduction rate, and the units of Z1, Z2 and absorptivity reduction rate are %.

13. The phosphor powder according to claim 12, wherein The Z1 is 90.0% or more. 14 . A composite comprising: the phosphor powder according to claim 1 ; and a sealing material that seals the phosphor powder.

15. The composite according to claim 14, wherein: The sealing material comprises one or more selected from silicone resin, epoxy resin, polyurethane resin, glass and ceramic. 16 . A light-emitting device comprising: a light-emitting element that emits excitation light, and the composite according to claim 14 or 15 that converts the wavelength of the excitation light.

Citation Information

Patent Citations

  • Phosphor, light-emitting device, illumination device and image display device

    JP2019077800A

  • Rotary electric machine

    JP2023118485A